2014
DOI: 10.1007/s00345-014-1378-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adding low-dose oral desmopressin therapy to tamsulosin therapy for treatment of nocturia owing to benign prostatic hyperplasia

Abstract: The addition of low-dose oral desmopressin therapy to an α-blocker tamsulosin provides effective treatment for nocturia in patients with LUTS/BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…The addition of low‐dose oral desmopressin 50 μg to the α 1 ‐blocker tamsulosin has shown to reduce the nocturnal frequency of voids by 64.3% compared with 44.6% when tamsulosin was given alone in patients with signs or symptoms of BPH (with or without nocturnal polyuria) . The study also demonstrated that this combination therapy improved the quality of sleep, whilst overall tolerability remained comparable to tamsulosin monotherapy . Similar results have been seen when low‐dose desmopressin was added to other α 1 ‐blockers for men with LUTS/BPH .…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The addition of low‐dose oral desmopressin 50 μg to the α 1 ‐blocker tamsulosin has shown to reduce the nocturnal frequency of voids by 64.3% compared with 44.6% when tamsulosin was given alone in patients with signs or symptoms of BPH (with or without nocturnal polyuria) . The study also demonstrated that this combination therapy improved the quality of sleep, whilst overall tolerability remained comparable to tamsulosin monotherapy . Similar results have been seen when low‐dose desmopressin was added to other α 1 ‐blockers for men with LUTS/BPH .…”
Section: Resultssupporting
confidence: 55%
“…In cases with a multifactorial aetiology of nocturia, treatment could target the various underlying causes with two or more drugs and, if necessary, in a multidisciplinary setting, but should always involve lifestyle changes and behavioural therapies. The addition of low‐dose oral desmopressin 50 μg to the α 1 ‐blocker tamsulosin has shown to reduce the nocturnal frequency of voids by 64.3% compared with 44.6% when tamsulosin was given alone in patients with signs or symptoms of BPH (with or without nocturnal polyuria) . The study also demonstrated that this combination therapy improved the quality of sleep, whilst overall tolerability remained comparable to tamsulosin monotherapy .…”
Section: Resultsmentioning
confidence: 85%
“…Desmopressin orally disintegrating tablets (ODT) were demonstrated to be safe and efficacious at a low‐dose (25 µg) in women, without additional clinical benefits at higher doses (50 and 100 µg) . A low‐dose (60 µg) formulation was safely combined with tamsulosin for controlling LUTS/benign prostatic hyperplasia in men …”
Section: Introductionmentioning
confidence: 99%
“…The addition of desmopressin to α‐blocker therapy of 123 men with BPE and nocturia reduced the number of nocturnal voids by 64%, which was significantly better that the 45% reduction of 125 men treated with α‐blocker alone …”
Section: Discussionmentioning
confidence: 93%